Relaxation of guinea-pig tracheal smooth muscle to arachidonate is converted to contraction following epithelium removal. - Farmer, S. G. (1987)
1 The effect of epithelium removal on responses of guinea-pig isolated trachealis to sodium arachidonate has been examined. 2 Arachidonate (100 microM) caused relaxation of epithelium-intact preparations, but following epithelium removal, the response to arachidonate was converted to contraction. In the presence of indomethacin (1 microM), arachidonate caused contraction in intact and denuded trachea. 3 Arachidonate also produced concentration-dependent effects, the qualitative nature of which varied with the presence or absence of the epithelium. In the presence of indomethacin, tracheal strips contracted in a concentration-dependent manner whether or not the epithelium had been removed. 4 Nordihydroguaiaretic acid (NDGA; 10 microM) markedly inhibited the contractile response of denuded strips to arachidonate. In intact tissues this lipoxygenase inhibitor converted the arachidonate-induced relaxation to a concentration-dependent contraction. The contraction to arachidonate, in the presence of NDGA, was epithelium-dependent. In the presence of both indomethacin and NDGA, responses to arachidonate were abolished. 5 It is concluded that the relaxation of guinea-pig trachea to arachidonic acid is epithelium-dependent and is mediated by an inhibitory product of the cyclo-oxygenase metabolic pathway. The contraction in denuded trachea, and trachea in the presence of indomethacin, may be mediated by lipoxygenase products of arachidonic acid metabolism, i.e. peptidoleukotrienes. The mediator of the epithelium-dependent contraction in NDGA-treated tissues is unknown.